DIAGNOSTIC ASSESSMENT ON SCHOOL APPRENTICESHIP (Fiep Bulletin - online, 2014)
It is acknowledged that there is a need of a new politico-pedagogic attitude at school, in the light of another perspective of society. For this, one has to consider new methodologies and new patterns of approaching the teaching/learning process which, before anything, make sure the permanence on the student at school and ensure the educational fulfillment, thus making possible the building up of the future citizen. The current view of school assumes an educational process where students are able to develop their criticism so as to be active in their social milieu, being aware of their roles in society and sensible to their rights and duties. Lastly, it is important to stress that the process component parts of the teaching/learning process cannot be seen under a linear, fragmented view. Planning, deed, studies reinforcement, the Class Council and assessment should always interplay in a dialectical manner, seeking to overcome and rethink its attitudes. When this need is recognizable, it is essential to be aware that knowledge must be insured to the student, in a critical manner, meaningful, creative and lasting. It is essential on the part of the educators to take a stand so that we really achieve our aim in terms of school, thereby accomplishing our objective of shaping citizens in full possession of their citizenship, in a more fair and humanitarian society.
Keywords: diagnostic assessment; learning; citizenship